A Theory of Socioeconomic Disparities in Health over the Life Cycle - Titus J. Galama; Hans van Kippersluis (Tinbergen Institute, 2010)
Understanding of the substantial disparity in health between low and high socioeconomic status (SES) groups is hampered by the lack of a suffciently comprehensive theoretical framework to interpret empirical facts and to predict yet untested relations. We present a life-cycle model that incorporates multiple mechanisms explaining (jointly) a large part of the observed disparities in health by SES. In our model, lifestyle factors, working conditions, retirement, living conditions and curative care are mechanisms through which SES, health and mortality are related. Our model predicts a widening and possibly a subsequent narrowing with age of the gradient in health by SES.
Keywords: D91; I10; I12; J00; J24; 330; socioeconomic status; education; health; demand for health; health capital; medical care; life cycle; age; labor; retirement; mortality; Sozialer Status; Bildung; Gesundheit; Gesundheitsversorgung; Sterblichkeit; Theorie